Transforming Health Care Through Information: Case Studies - Einbinder, Laura; Lorenzi, Nancy M.; Ash, Joan; Gadd, Cynthia S.; Einbinder, Jonathan (Health Informatics, 2010)
Clinical informatics is poised for a period of rapid growth and expansion. A confluence of forces and trends, including pressure to contain healthcare costs and simultaneously expand access and coverage, a desire to reduce medical error and healthcare disparities, the need to better understand and optimize our clinical interventions and delivery systems, the need to translate new knowledge into practice quickly and effectively, and the need to demonstrate the value of our services, all call for the application of the methods and techniques of our field. Transforming Health Care Through Information contains the collected practical experience of the highly respected authorship and contributes to the evolving framework of understanding in this discipline. The Editors are all leaders in their field and have assembled a team of authors with an intimate understanding of the subject to create this rich collection. The book is organized around four major areas or domains of clinical informatics - Managing Change, Patient Safety, Organizational Impact and Evaluation, and Integration - and focuses on the people and organizational process of applied informatics, as well as evaluation, across a wide range of topics. It will be of considerable help to any practitioner in the field of clinical informatics, increasing understanding of the issues at hand.